Synthesis, characterization and photocatalytic activities of nanoparticulate N, S co-doped TiO2 having different surface-to-volume ratios - Rengifo Herrera, Julian Andres (2010)
An efficient, visible light active, N, S-codoped TiO2-based photocatalyst was prepared by reacting thiourea with nanoparticulate anatase TiO2. Commercial anatase powders were manually ground with thiourea and annealed at 400 °C in two crucibles with different surface-to-volume ratios (S/V = 20 and 1.5) to prepare two N, S-codoped TiO2 materials. The differentiated aeration conditions during the catalyst annealing on the crucibles allowed for different amounts of O2 to reach the catalyst surface. The first material, with S/V = 20, herein referred to as D-TKP 102-A, was clear beige colored. The second material, with S/V = 1.5, herein referred to as D-TKP 102-B, was darker and revealed a markedly lower efficiency in Escherichia coli inactivation. The D-TKP 102-A powder presented visible light absorption due to the nitrogen (N) and sulfur (S) doping. X-ray photoelectron spectroscopy signals for this catalyst were observed for N 1s peaks at binding energies of 399.2 and 400.7 eV due to interstitial N-doping or Ti−O−N species. The S 2p were due to SO4−2 signals with BE >168 eV and signals at 162.8 and 167.2 eV due to anionic and cationic S-doping, respectively. By fast kinetic spectroscopy, the decay of the electron induced by pulsed light at λ = 450 nm (∼8 ns/laser pulse) was followed for the D-TKP 102-A catalyst. Undoped D-TKP 102 catalyst did not promote the electron in the visible range, and consequently no signal decay could be observed in the latter case. Low-temperature electron spin resonance measurements at 8 K provided evidence for electrons trapped in shallow traps, such as oxygen vacancies, Vo, induced by N, S doped on D-TKP 102-A. The ESR measurements implementing the reactive scavenging with singlet oxygen scavenger, TMP−OH, revealed the production of singlet oxygen (1O2).